Great commission companies : the emerging role of business in missions - Rundle, Steve, 1959-; Steffen, Tom A., 1947- (Downers Grove, Ill. : IVP Books, 2011)
Steve Rundle and om Steffen offer their paradigm for the convergence of business and missions--the Great Commission Company. Such companies intentionally create businesses in strategic locations, pursuing profits while remaining unabashedly Christian in their purpose. By establishing authentic businesses that employ local workers among the least-reached peoples of the world, they contribute to the economic health of the immediate community and also provide avenues for both physical and spiritual ministry. --from publisher description.
Part 1: Principles of great commission companies:The good news about globalization -- Toward a definition of a great commission company -- Globalization and business -- Globalization and missions -- Turning vision into action -- Sustaining success -- Part 2: Great commission companies in practice: The Silk Road Handicraft Company -- Bajalia Trading Company/Bajalia International Group -- Little Texas -- Global engineering and management solutions -- Olive technology -- Pura Vida Coffee -- Conclusion.
Includes bibliographical references (p. [232]-236) and indexes.
Keywords: Business enterprises -- Religious aspects; Missions -- Finance